Development of a lightweight FMCW SAR radar for drone-based wall penetration operations - Kong, Alvin Yen Chin (2019)
RADARs utilizing both frequency-modulated continuous-wave (FMCW) techniques with Synthetic Aperture Radar (SAR) principles are of interest in recent years. The FMCW approach keeps hardware cost low quicker signal processing. The union of the two concepts has led to compact, cost-effective and high-resolution RADAR systems. This has led to increase interest in development of compact RADAR to be fitted on Unmanned Aerial Vehicles (UAVs) for civilian and military use. The ability to identify human targets position and velocity behind walls and light foliage is also of interest to military and security personnel. However, RADAR hardware design is not cheap and requires deep expertise. A software design approach can provide a more cost-effective way. MATLAB and Simulink tools may provide the answer. The suite of toolbox available in MATLAB will be studied to meet the needs of up and coming RADAR technology. Those identified in the paper includes FMCW Radar, SAR imaging and wall attenuation. The research will identify suitable models in these areas of interest and carry out tests to determine the feasibility in RADAR design.